Integrating multiple omics to unravel mechanisms of Cyclosporin A induced hepatotoxicity in vitro. Issue 3 (April 2015) - Van den Hof, Wim F.P.M.; Ruiz-Aracama, Ainhoa; Van Summeren, Anke; Jennen, Danyel G.J.; Gaj, Stan; Coonen, Maarten L.J.; Brauers, Karen; Wodzig, Will K.W.H.; van Delft, Joost H.M.; Kleinjans, Jos C.S.
Highlights Integrated analyses of transcriptome and metabonome results in relevant pathways. We could unravel mechanisms underlying Cyclosporin A-induced hepatotoxicity. The proposed model for drug-induced cholestasis provides valuable information. Cyclosporin A treatment impairs cholesterol metabolism and bile acid synthesis.